[2H26]-1-epi-Cubenol, a completely deuterated natural product from Streptomyces griseus - Citron, Christian A.; Dickschat, Jeroen S. (Beilstein Journal of Organic Chemistry, 2013)
During growth on fully deuterated medium the volatile terpene [2H26]-1-epi-cubenol was released by the actinomycete Streptomyces griseus. This compound represents the first completely deuterated terpene obtained by fermentation. Despite a few previous reports in the literature the operability of this approach to fully deuterated compounds is still surprising, because the strong kinetic isotope effect of deuterium is known to slow down all metabolic processes in living organisms. Potential applications of completely labelled compounds from natural sources in structure elucidation, biosynthetic or pharmacokinetic investigations are discussed.
Keywords: biosynthesis; deuterium; labelling; natural products; Streptomyces; terpenes

(untitled) - Nakano, C.; Horinouchi, S.; Ohnishi, Y. (J. Biol. Chem., 2011)

(untitled) - Nakano, C.; Tezuka, T.; Horinouchi, S.; Ohnishi, Y. (J. Antibiot., 2012)

(untitled) - Dickschat, J. S.; Nawrath, T.; Thiel, V.; Kunze, B.; Müller, R.; Schulz, S. (Angew. Chem., Int. Ed., 2007)

(untitled) - Wang, C.-M.; Cane, D. E. (J. Am. Chem. Soc., 2008)

(untitled) - Komatsu, M.; Tsuda, M.; Omura, S.; Oikawa, H.; Ikeda, H. (Proc. Natl. Acad. Sci. U. S. A., 2008)

(untitled) - Birch, A. J.; Richards, R. W.; Smith, H. (Tetrahedron, 1959)

(untitled) - Vederas, J. C. (Nat. Prod. Rep., 1987)

(untitled) - Brock, N. L.; Ravella, S. R.; Schulz, S.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2013)

(untitled) - Brock, N. L.; Dickschat, J. S. (ChemBioChem, 2013)

(untitled) - Citron, C. A.; Riclea, R.; Brock, N. L.; Dickschat, J. S. (RSC Adv., 2011)

(untitled) - Citron, C. A.; Brock, N. L.; Rabe, P.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2012)

(untitled) - Brock, N. L.; Tudzynski, B.; Dickschat, J. S. (ChemBioChem, 2011)

(untitled) - Chou, W. K. W.; Fanizza, I.; Uchiyama, T.; Komatsu, M.; Ikeda, H.; Cane, D. E. (J. Am. Chem. Soc., 2010)

Interpretation of Mass Spectra - McLafferty, F. W.; Turecek, F. (University Science Books, 1993)

(untitled) - Dickschat, J. S.; Citron, C. A.; Brock, N. L.; Riclea, R.; Kuhz, H. (Eur. J. Org. Chem., 2011)

(untitled) - Cane, D. E.; Buchwald, S. L. (J. Am. Chem. Soc., 1977)

(untitled) - Scott, F. E.; Simpson, T. J.; Trimble, L. A.; Vederas, J. C. (J. Chem. Soc., Chem. Commun., 1984)

(untitled) - Bell, R. P. (Chem. Soc. Rev., 1974)

(untitled) - Zu, L.; Xu, M.; Lodewyk, M. W.; Cane, D. E.; Peters, R. J.; Tantillo, D. J. (J. Am. Chem. Soc., 2012)

(untitled) - Lovett, S. (Nature, 1964)

(untitled) - de Giovanni, R.; Zamenhof, S. (Biochem. J., 1963)

(untitled) - de Giovanni, R. (Z. Vererbungsl., 1961)

(untitled) - Hirai, K.; Tomida, M.; Kikuchi, Y.; Ueda, O.; Ando, H.; Asanuma, N. (Bull. Tokyo Dent. Coll., 2010)

(untitled) - Dybing, O.; Guldberg, G.; Hansen, K. (Klin. Wochenschr., 1938)

(untitled) - Grob, K.; Zürcher, F. (J. Chromatogr., 1976)

(untitled) - Citron, C. A.; Gleitzmann, J.; Laurenzano, G.; Pukall, R.; Dickschat, J. S. (ChemBioChem, 2012)

(untitled) - Bode, H. B.; Bethe, B.; Höfs, R.; Zeeck, A. (ChemBioChem, 2002)

(untitled) - Bode, H. B.; Reimer, D.; Fuchs, S. W.; Kirchner, F.; Dauth, C.; Kegler, C.; Lorenzen, W.; Brachmann, A. O.; Grün, P. (Chem.–Eur. J., 2012)

(untitled) - Barber, J.; Staunton, J. (J. Chem. Soc., Perkin Trans. 1, 1980)

(untitled) - Joyce, S. A.; Brachmann, A. O.; Glazer, I.; Lango, L.; Schwär, G.; Clarke, D. J.; Bode, H. B. (Angew. Chem., Int. Ed., 2008)

(untitled) - Brachmann, A. O.; Forst, S.; Furgani, G. M.; Fodor, A.; Bode, H. B. (J. Nat. Prod., 2006)

(untitled) - Gelijkens, C. F.; van Peer, A.; Lenoir, H.; Knaeps, A.; Woestenborghs, R.; Heykants, J. (Biomed. Mass Spectrom., 1985)

(untitled) - Blakeley, M. P.; Langan, P.; Niimura, N.; Podjarny, A. (Curr. Opin. Struct. Biol., 2008)

(untitled) - Junk, T.; Catallo, W. J. (Chem. Soc. Rev., 1997)

(untitled) - Adio, A. M. (Tetrahedron, 2009)

(untitled) - Smyth, T. J.; Perfumo, A.; Marchant, R.; Banat, I. M.; Chen, M.; Thomas, R. K.; Penfold, J.; Stevenson, P. S.; Parry, N. J. (Appl. Microbiol. Biotechnol., 2010)